PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM PERPUSNAS DALAM RANGKA PENGEMBANGAN LITERASI DI KELURAHAN RAKAM, KECAMATAN SELONG, KABUPATEN LOMBOK TIMUR - Haq, Muhammad; Gani, Raden; Sujakti, I; Hulfiani, Siti; Safitri, Dita; Saputra, Adriyan; Maharani, Dewi; Dewi, Mirnawati; Zalty, Rani; Ramadhani, Muhamad; Ramadhani, Muhammad (Jurnal Wicara, 2025)
This study discusses the implementation of the literacy program initiated by the National Library of Indonesia (Perpusnas) through the Community Service Program (KKN) in Rakam Village, Selong District, East Lombok Regency, as an effort to improve reading culture among elementary school children. Rakam Village has a population of 8,688 people and 2,592 households, with the majority working as traders, laborers, farmers, fishermen, and entrepreneurs, and with an average education level ranging from elementary to senior high school. These socio-economic conditions contribute to the community’s low literacy awareness, even though the village has several educational institutions ranging from early childhood education (PAUD) to senior high schools (SMA/SMK) that can serve as strategic partners. Using a descriptive qualitative method, data were collected through observation, interviews, documentation, and direct participation with Community Reading Garden (TBM) managers, teachers, the village government, parents, and students. The findings show that literacy programs such as read-aloud activities, creative writing training, cataloging and organizing TBM collections, book-based creative projects, and book review competitions successfully improved reading interest, writing creativity, and the utilization of TBM facilities. Supporting factors included the involvement of the local government, teachers, and parents, as well as the provision of diverse and engaging literacy activities. However, program sustainability still requires long-term commitment from TBM, schools, and the village government to ensure continuous literacy development. These findings emphasize that multi-stakeholder collaboration and participatory literacy strategies can be effective solutions to address low literacy rates at the village level.